Utility of the Method for Calculating the Heart to Contralateral Ratio for Cardiac Amyloidosis by Using Ray-summation Images in 99mTc-pyrophosphate Scintigraphy - Takata, Kei; Horita, Hirokazu; Shibutani, Naoki (Japanese Journal of Radiological Technology, 2022)
Purpose: The purpose of this study was to avoid the influence of background activity in the calculation of heart to contralateral ratio (H/CL) in 99mTc-pyrophosphate (PYP) scintigraphy for diagnosis of cardiac amyloidosis. Therefore, we investigated the utility of the H/CL calculation method using ray-summation (ray-sum) images created by multi-planar reconstruction and summing slices of the heart range from single-photon emission computed tomography (SPECT) images. Methods: The subjects were 33 patients who underwent 99mTc-PYP planar and SPECT/CT at 3 hours after injection. Ray-summation axial (ray-sum axial) and ray-summation coronal (ray-sum coronal) images were created and H/CL was calculated. We compared the differences in sensitivity, specificity, accuracy, and area under the curve (AUC) between the conventional method and our method, and calculated the cutoff values. Results: Comparison of the conventional method and our method showed no significant difference in sensitivity and AUC, while specificity was significantly improved to 97% (p=0.003) of ray-sum axial image and 90% (p=0.01) of ray-sum coronal image, and accuracy was significantly improved to 94% (p=0.02) of ray-sum axial image. Conclusion: The H/CL calculation method using ray-sum images had higher diagnostic performance than the conventional method, with optimal cutoff of ray-sum axial images 3.07 and ray-sum coronal images 2.77.